CYTOTOXIC AND ANTI-MIGRATORY ACTIVITIES FROM HYDROALCOHOLIC EXTRACT OF Euphorbia lactea Haw. AGAINST HN22 CELL LINE - WONGPRAYOON, PAWARIS; CHAROENSUKSAI, PURIN (Thai Bulletin of Pharmaceutical Sciences, 2018)
Euphorbiaceae is a botanical family of evolutionarily and morphologically distinct group of plants. Many euphorbias have been associated with diverse pharmacological properties including anticancer activity. Euphorbia lactea Haw. can be found naturally throughout Thailand; however, its anticancer activity remains largely unexplored. Here, we screened hydroalcoholic extract of E. lactea for its anticancer potentials, focusing on cytotoxic and anti-migratory activities using a migratory competent head and neck cancer cell line HN22 as an in vitro model. We detected statistically significant and dose-dependent cytotoxic activity of E. lactea hydroalcoholic extract against HN22 cells through MTT assay. Flow cytometry analysis of HN22 cells treated with the extract revealed an increase in sub-G1 population, suggesting that the cytotoxic effect of E. lactea hydroalcoholic extract likely involved an initiation of apoptosis in this cell line. Additionally, through wound-healing assays, we unprecedentedly reported an anti-migratory activity against HN22 cells from E. lactea hydroalcoholic extract. Together, exhibiting two attractive attributes i.e. cytotoxic and anti-migratory activities toward HN22 cells, our results identified E. lactea as a promising candidate medicinal plant for further investigations to unlock its anticancer potentials.